Derecho a la igualdad y remuneración equitativa - Zuta Palacios, Karla (Pontificia Universidad Católica del Perú, 2019)
It is known that gender pay gap is a worldwide problem. Even though it is now a lot smaller than it used to be, there is still a lot to improve. In this context, the present article analyzes the legal treatment that this situation currently receives in Peru, focusing on equal pay and treatment within labour relationships. Its arguments are reinforced by national and international doctrine and jurisprudence. As a result of this analysis, the author details the criterion that are to be followed by judges and government inspectors, when determining the validity of unequal payment in certain cases. This criterion can also help distinguishing those cases in which the employer has committed a hostile or discriminating act.

La brecha salarial entre hombres y mujeres es un problema de dimensiones globales en el que, si bien se ha avanzado mucho, aún queda mucho por recorrer. En este contexto, el presente artículo aborda, a partir de doctrina y jurisprudencia nacional e internacional, la problemática en torno a la igualdad salarial en el Perú. Para ello, desarrolla de manera previa el contenido esencial del derecho de igualdad, el derecho a la remuneración y el derecho a la no discriminación, y cómo estos toman forma en el marco de las relaciones laborales. Como resultado de este análisis, se detallan los criterios que deben seguir tanto los jueces como los organismos fiscalizadores para determinar cuándo una diferenciación salarial es legítima o no, y si esta ha constituido un acto hostil o discriminatorio.
Gender Equality and the right to equal pay and treatment
Keywords: Brecha salarial; Equidad salarial; Derecho a la igualdad; Discriminación laboral; https://purl.org/pe-repo/ocde/ford#5.05.01